Antioxidant activity of nanoencapsulated chia (Salvia hispanica L.) seed extract and its application to manufacture a functional cheese. Issue 3 (15th December 2022) - Hosseini, Farinaz; Motamedzadegan, Ali; Raeisi, Shahram Naghizadeh; Rahaiee, Somayeh
Abstract: The study aimed to produce a functional ricotta cheese with chia seed extract (CSE) nanocapsules. First, the CSE was encapsulated using lecithin and basil seed gum, and its characteristics and antioxidant activity (AA) were evaluated. The free CSE (F‐CSE) and encapsulated CSE (E‐CSE) were then added to ricotta cheese formulation (1.5 and 3.0% w/w). The samples were kept for 15 days in a refrigerator and their physicochemical, sensory properties, AA, and oxidative stability were examined. The particle size, polydispersity index, zeta potential, and encapsulation efficiency of CSE nanocapsules were 59.23 nm, 0.328, −44.47 mV, and 80.06%, respectively. The CSE showed remarkable AA in vitro. The AA of F‐CSE was higher than E‐CSE. The moisture, dry matter, fat, and protein content of cheese samples were in the range of 52.64%–53.31%, 46.69%–47.36%, 19.02%–19.28%, and 16.88%–17.02%, respectively. The color of F‐CSE cheeses was slightly yellower than control; however, they did not have clear color differences. During storage, the acidity, hardness, chewiness, and peroxide value of cheeses increased, while the pH, total phenol content, and AA decreased ( p  < .05). The addition of CSE reduced the rate of pH and acidity changes during storage and significantly increase the AA and oxidative stability. Initially, F‐CSE cheeses had higher functional activity, but on other storage days, due to the protective effect of coating materials, the functional activity of E‐CSE samples was higher. The CSE, especially E‐CSE, did not have an adverse effect on the sensory properties of cheese. Based on the results of this study, it can be concluded that it is possible to manufacture a functional cheese using E‐CSE. Abstract : We encapsulated the chia seed extract (CSE) nanoliposomes with basil seed gum (BSG) successfully. The free CSE (F‐CSE) and encapsulated CSE (E‐CSE) were added to ricotta cheese formulation (1.5% and 3.0% w/w) to produce a functional cheese. The E‐CSE cheeses had higher functional activity, during 15 days storage, comparing the E‐CSE samples.